1997
DOI: 10.1159/000227698
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Criteria That Prove the Similarities between Amphibian and Human Tumors

Abstract: Toads fed with 0.5 mg 7,12-dimethylbenz(a)anthracene twice a week for 12 weeks displayed liver tumors in 27 out of 100 cases. Electron micrographs of liver tumors showed some criteria of malignancy, such as the presence of nuclear pockets, pseudoinclusions, dilatation of the cisternae of rough endoplasmic reticulum and loss of cell junctions. These features are closely similar to those of true malignancy described in humans and other mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results of the present investigation confirm our previous studies by light and electron microscope (Sadek and Abdul-Salem, 1994a, b;Abdelmeguid et al, 1997) which showed that DMBA induces liver tumor. Also, the present study clearly indicated that indomethacin decreases the incidence of liver tumor in the Egyptian toad.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present investigation confirm our previous studies by light and electron microscope (Sadek and Abdul-Salem, 1994a, b;Abdelmeguid et al, 1997) which showed that DMBA induces liver tumor. Also, the present study clearly indicated that indomethacin decreases the incidence of liver tumor in the Egyptian toad.…”
Section: Discussionsupporting
confidence: 93%
“…However, type 2 nuclear pockets seems to arise by invagination of the inner nuclear envelope, producing a meandering cleft which sequestrates nuclear material ultimately producing a type 2 pocket. On the other hand, Abdelmeguid et al (1997) observed the two types of nuclear pockets in amphibian tumor. Ultrastructural changes on the surface and within the cytoplasm of mucosa cells including epithelial mucous cells were observed, indicating disturbed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies on the effect of retinoid on carcinogenesis have given apparently contradictory results. In tumor promotion studies, retinoid both inhibit (Hill and Grubbs, 1992) and enhance (Hasegawa et al, 1988) the induction of tumors in toads and human were reported (Abdelmeguid et al, 1997). The present study therefore was undertaken to determine whether acrylamide have any carcinogenic effects on liver of the Egyptian toad, Bufo regularis and to clarify the role of B-carotene on the liver in the experimental toads, previously treated with acrylamide.…”
Section: Introductionmentioning
confidence: 97%